Molecular Adjuvant Potential of GCSF and MCSF in Starry Flounder Challenged with Streptococcus parauberis - Min-Young Sohn; Gyoungsik Kang; Kyung-Ho Kim; Ha-Jeong Son; Chan-Il Park (Animals)
In fish, the innate immune system is crucial for rapid defense against pathogens. In this study, we performed transcriptome sequencing using next-generation sequencing (NGS) to identify and characterize granulocyte colony-stimulating factor (GCSF) and macrophage colony-stimulating factor (MCSF) in starry flounder (Platichthys stellatus). The GCSF gene (594 bp, 198 aa) features a conserved IL-6 domain, while the MCSF gene (621 bp, 207 aa) contains a predicted transmembrane region. Phylogenetic analysis confirmed high evolutionary conservation with other marine species. Quantitative real-time PCR revealed that GCSF is highly expressed in the skin, peripheral blood leukocytes, and muscle, with significant up-regulation in immune organs following Streptococcus parauberis infection; MCSF exhibited a similar tissue-specific expression pattern. Recombinant GCSF (rGCSF) was produced using a cell-free system and effectively enhanced leukocyte phagocytic activity at an optimal concentration of 150 μg/mL, without causing cytotoxicity in hemolytic assays. In contrast, rMCSF exhibited folding issues during purification. These findings highlight the potential of rGCSF as a molecular adjuvant to enhance immune responses in aquaculture. This study provides foundational knowledge for developing cytokine-based adjuvants, which could reduce antibiotic dependency and enhance vaccine efficacy in sustainable aquaculture systems.